201k views
3 votes
What is the value of this expression when m=3 and n=-5 (6m^-1n^0)^-3

User Ron Brogan
by
6.2k points

2 Answers

6 votes

Answer:


(1)/(8)

Explanation:

Given expression is,


(6m^(-1)n^0)^(-3)


=(6m^(-1))^(-3) (
a^0 =1 )


=6^(-3) (m^(-1))^(-3) (
(ab)^m=a^mb^m )


=6^(-3) m^(-1* -3) (
(a^m)^n=a^(mn) )


=6^(-3) m^3


=(m^3)/(6^3) (
a^m=(1)/(a^(-m)) )


=(m^3)/(216)

We have, m = 3


=(3^3)/(216)


=(27)/(216)


=(1)/(8)

User Bartlomiej
by
6.0k points
7 votes
this is

(6(3)^-1 (-5)^0)^-3

= (6/3 * 1)^-3

= (2)^-3

= 1/8 Answer
User Max Kaha
by
5.8k points